Corporate social responsibility and corporate governance in Indonesian public listed companies - Ika Siti Rochmah; Dwiwinarno Titop; Widagdo Ari Kuncara (SHS Web of Conferences, 2017)
This study aims to investigate whether theree has been a change in the level of corporate social responsibility (CSR) disclosure and to examine whether corporate governance attributes influence CSR disclosure in corporate annual report of Indonesian public listed companies(PLCs). The annual reports of 115 PLC for two years (2011 and 2012) were analysed using content analysis. Multiple regression analysis was utilized to determine factors influencing CSR disclosure in annual reports. Consistent with expectations, the paired sample t-test showed that there was an increase (significant at the 1 percent level) in the extent of CSR disclosure. The multiple regression analysis revealed that audit committee effectiveness and company’s size were positively associated with the extent of CSR disclosure (significant at 5 per cent level). The findings appear to suggest that The Indonesian Capital Market and Financial Institutions Supervisory Agency (Bapepam LK) effforts in promoting CSR through the release of Regulation No X.K.6 in 2012 have had some positive impact on CSR disclosure in annual report. The results also suggest that the involvement of audit committee through its effectiveness in overseeing company’s financial reporting could lead to better concern in corporate social activities and hence disclosure in annual reports. This study however, has limitation that should be considered in interpreting the results. The regression model documented an R2 of 21.4 percent, which indicates that almost 80 percent of factors influencing CSR disclosure in Indonesian PLC have not been captured by the model. These other factors may perhaps be indentified in the next research.